Thromboprophylaxis in Intensive Care Unit Patients - Rikardi, Fachrizal; Fitriani R.W, Calcarina (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2024)
Background: Intensive Care Unit (ICU) patients are at twice the risk of experiencing thrombosis compared to patients in regular wards. This risk is associated with prolonged immobility, sedation, and neuromuscular blockade to facilitate ventilation. The incidence ranges from 8-40%. This undoubtedly leads to poorer patient outcomes, including increased patient mortality. ICU patients require prophylaxis to prevent thrombotic events. The use of thromboprophylaxis has been shown to reduce mortality rates in these patients.Content: Intensive Care Unit (ICU) patients are at risk of developing thrombosis, which is closely related to Virchow's triad, which consists of venous stasis, endothelial dysfunction, and hypercoagulability. Considering the high morbidity associated with thrombotic events and the low side effects of carefully administered anticoagulants, pharmacological prophylaxis should be provided to all critically ill patients without contraindications to anticoagulants. Regular monitoring is necessary when administering pharmacological prophylaxis. Compared with UFH and mechanical compression, LMWH is the preferred thromboprophylaxis for ICU patients. Generally, patients weighing 50-100 kg can be given LMWH, such as enoxaparin, at a subcutaneous dose of 40 mg per day. The discontinuation of thromboprophylaxis should consider the patient's clinical condition and drug side effects.Summary: Thromboprophylaxis is highly necessary for Intensive Care Unit (ICU) patients. The preferred thromboprophylaxis for ICU patients is LMWH. In certain circumstances, UFH or mechanical thromboprophylaxis may be considered.